Surirella antioquiensis sp. nov. and S. rafaelii sp. nov. (Bacillariophyta) from Colombia (2013)
ABSTRACT: This article is part of a series of studies to produce and inventory of the diatom flora of Colombia. Two Surirella taxa −S. antioquiensis S.E. Sala, J.J. Ramírez, Plata-Díaz & Vouilloud and S. rafaelii J.J. Ramírez & S.E. Sala− from lotic and lentic aquatic systems in the Department of Antioquia (Colombia) are proposed as new species. Both new species were analyzed with light and scanning electron microscopy. Each taxon is described and illustrated and information about environmental conditions of sampling sites is given.